Long-term health consequences of COVID-19 disease - Karthikeyan P Iyengar; Raju Vaishya (Apollo Medicine)
The effects of novel coronavirus Severe Acute Respiratory Syndrome-CoV-2 outbreak until now have been dramatic on public health with widespread disruption of daily life and health care systems across the world. As we understand the new COVID-19 better, it is becoming apparent that the disease is far more complex. The extent and severity of the long-term health consequences remain uncertain, but emerging data suggest persistent, substantial morbidity of the population is likely. Long-term consequences are expected to have lasting physical, mental, and social health impact along with global economic effects.